Trends and impact of three-dimensional preoperative imaging for anatomic total shoulder arthroplasty. (August 2021) - Cancienne, Jourdan M; Dempsey, Ian J; Garrigues, Grant E; Cole, Brian J; Brockmeier, Stephen F; Werner, Brian C
Background: The goals of this study were to determine the incidence in the United States of preoperative three-dimensional imaging prior to anatomic total shoulder arthroplasty for osteoarthritis and to determine if preoperative imaging is associated with decreased complication rates. Methods: Using a Medicare insurance database, we identified all patients who underwent computed tomography (n = 9380) and/or magnetic resonance imaging (n = 15, 653) prior to anatomic total shoulder arthroplasty for a diagnosis of osteoarthritis from 2005 to 2014. The incidence of imaging over time was analyzed and complication rates compared between patients with imaging to matched controls. Results: The incidence of preoperative three-dimensional imaging significantly increased over time, with computed tomography increasing more than magnetic resonance imaging. Compared to controls, patients with preoperative computed tomography imaging had significantly lower revision rates at two years (odds ratio 0.72 (0.64–0.82), p  = 0.008). There were no other significant differences in the other complications studied. Conclusions: The use of preoperative three-dimensional imaging for anatomic total shoulder arthroplasty for a diagnosis of osteoarthritis has increased dramatically, with the use of computed tomography increasing the most. Patients who underwent preoperative computed tomography imaging experienced lower revision rates at two years postoperatively compared to matched controls without such imaging. Level of evidence: Level III, retrospective comparative study.